2020
DOI: 10.1111/odi.13679
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin levels in periodontitis vs. the healthy state: A systematic review and meta‐analysis

Abstract: The aim was to provide a comprehensive qualitative and quantitative assessment of any potential differences in melatonin levels in periodontitis vs. the healthy state.The keyword combination "melatonin" AND "periodontitis" was searched in Web of Science, PubMed, and Scopus. Qualitative analysis and quantitative analysis were | Inclusion criteriaOriginal research in English language assessing the melatonin levels in saliva, plasma, gingival crevicular fluid, or gingival tissue samples of humans with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Studies on melatonin levels in periodontitis have reported significantly lower levels in saliva [ 19 ], gingival tissue samples [ 18 ], and GCF [ 20 ]. However, a recent systematic review highlighted a significantly low level of salivary melatonin in patients with periodontitis versus healthy individuals [ 21 ]. Since melatonin levels are lowered in periodontitis, an augmentation of the same by exogenous supplementation has been implemented in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on melatonin levels in periodontitis have reported significantly lower levels in saliva [ 19 ], gingival tissue samples [ 18 ], and GCF [ 20 ]. However, a recent systematic review highlighted a significantly low level of salivary melatonin in patients with periodontitis versus healthy individuals [ 21 ]. Since melatonin levels are lowered in periodontitis, an augmentation of the same by exogenous supplementation has been implemented in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has been assayed in saliva [ 19 ], gingival crevicular fluid (GCF) [ 20 ], and gingival tissues [ 18 ], and its overall levels were found to be lowered in patients with periodontitis than healthy controls. A recently published systematic review performed by some of us, found a depletion of salivary melatonin levels in patients with periodontitis versus healthy individuals [ 21 ]. This finding is significant as it highlights the need for melatonin supplementation in the management of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin levels are associated with the severity of periodontitis. A systematic review by Balaji TM et al has shown an initial reduction in melatonin levels followed by elevation with worsening of periodontitis 128 . The application of melatonin as a topical/systemic formulation to treat periodontitis was also reported by Balaji TM et al Apart from the level and application of melatonin in periodontitis, melatonin is demonstrated to regulate immune response and prevent periodontal tissue from damage.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…Melatonin insufficiency contributes to aging, menopause and diabetes-associated osteoporosis, and supplementation of which helps improve bone status [ 82 , 83 ]. However, the results of studies focusing on the relationship between periodontitis and melatonin are conflicting [ 84 ]. Clinical studies indicate that oral melatonin supplementation arrests periodontitis progression and alveolar bone destruction, evidenced by improved clinical parameters and reduced salivary RANKL/OPG ratio, regardless of the application of nonsurgical periodontal therapy [ 85 ].…”
Section: Hormonesmentioning
confidence: 99%